Analysis of the role of M24 protein in group A streptococcal adhesion and colonization by use of omega-interposon mutagenesis. - Courtney, H S (1994)
We recently concluded that M protein mediates adherence of group A streptococci to HEp-2 tissue culture cells, because the N-terminal half of M protein blocked adherence and M+ strains attached in greater numbers than M- streptococci. To further assess the role of M protein in adhesion, an M-, isogenic mutant of M type M-, isogenic mutant of M type 24 group A streptococci was constructed by insertional inactivation of the emm24 gene with the omega-interposon flanked by emm24 gene sequences. Southern blot analysis confirmed that the omega-element inserted only into emm24. The M- isogenic mutant M24-omega 3 did not react with antiserum to M24 protein, not did it survive in whole human blood. Electron micrographs of M24-omega 3 showed a diminution of surface fibrillae and reduced binding of plasma components compared with the parent strain. The adhesion of the M+ parent to HEp-2 cells and to mouse oral epithelial cells was dramatically greater than the adhesion of the M24-omega 3 mutant, although there was no difference between the two in adhesion to human buccal cells. In addition, the parent strain was dramatically more effective than the M24-omega 3 mutant in colonizing the oral cavity of mice. These results indicate that the M24 protein can serve as an adhesin in streptococcal attachment to human cells in tissue culture and is important in the colonization of mouse mucosal surfaces.